Synchrotron-based visualization and segmentation of elastic lamellae in the mouse carotid artery during quasi-static pressure inflation. Issue 155 (26th June 2019) - Trachet, Bram; Ferraro, Mauro; Lovric, Goran; Aslanidou, Lydia; Logghe, Gerlinde; Segers, Patrick; Stergiopulos, Nikolaos
Abstract : In computational aortic biomechanics, aortic and arterial tissue are typically modelled as a homogeneous layer, making abstraction not only of the layered structure of intima, media and adventitia but also of the microstructure that exists within these layers. Here, we present a novel method to visualize the microstructure of the tunica media along the entire circumference of the vessel. To that end, we developed a pressure-inflation device that is compatible with synchrotron-based phase-contrast imaging. Using freshly excised left common carotid arteries from n = 12 mice, we visualized how the lamellae and interlamellar layers inflate as the luminal pressure is increased from 0 to 120 mm Hg in quasi-static steps. A graph-based segmentation algorithm subsequently allowed us to automatically segment each of the three lamellae, resulting in a three-dimensional geometry that represents lamellae, interlamellar layers and adventitia at nine different pressure levels. Our results demonstrate that the three elastic lamellae unfold and stretch simultaneously as luminal pressure is increased. In the long term, we believe that the results presented in this work can be a first step towards a better understanding of the mechanics of the arterial microstructure.